Case Report: Overlap Between Long COVID and Functional Neurological Disorders - Gilio, Luana; Galifi, Giovanni; Centonze, Diego; Stampanoni Bassi, Mario (Frontiers in Neurology, 2022)
Long lasting symptoms have been reported in a considerable proportion of patients after a severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection. This condition, defined as either “post-acute coronavirus disease (COVID),” “long COVID,” or “long-haul COVID,” has also been described in outpatients and in individuals who are asymptomatic during the acute infection. A possible overlap exists between this condition and the functional neurological disorders (FNDs). We report a 23-year-old man who developed, after asymptomatic COVID-19, a complex symptomatology characterized by fatigue, episodic shortness of breath, nocturnal tachycardia, and chest pain. He also complained of attention and memory difficulties, fluctuating limb dysesthesia, and weakness of his left arm. After neurological examination, a diagnosis of FND was made. Notably, the patient was also evaluated at a post-COVID center and received a diagnosis of long COVID-19 syndrome. After 4 months of psychoanalytic psychotherapy and targeted physical therapy in our center for FNDs, dysesthesia and motor symptoms had resolved, and the subjective cognitive complaints had improved significantly. However, the patient had not fully recovered as mild symptoms persisted limiting physical activities. Long-term post COVID symptoms and FNDs may share underlying biological mechanisms, such as stress and inflammation. Our case suggests that functional symptoms may coexist with the long COVID symptoms and may improve with targeted interventions. In patients presenting with new fluctuating symptoms after SARS-CoV-2 infection, the diagnosis of FNDs should be considered, and the positive clinical signs should be carefully investigated.